Pengaruh Kecepatan Angin Pada Pembangkit Listrik Tenaga Angin Memanfaatkan Kubah Masjid Putar - Rahmat Kholiq Al Mujasir, Nur Kholis, Humaidillah Kurniadi Wardana (Reaktom : Rekayasa Keteknikan dan Optimasi, 2021)
This research aims to develop and research further about the potential of wind in Jombang to be used as analternative to wind power plants by utilizing the domed swivel mosque. The method in this research is experimentalresearch related to science and engineering technology, namely the making of a mosque turning dome as an alternativeto wind power generation. This tool utilizes the spinning dome of a turning mosque as a producer of motion energywhich is connected to a dc generator using gear and chains as a transformer of rotary motion energy into electricalenergy that produces dc electricity output. The DC electricity is supplied to the Buck boost converter to be regulatedand stabilized the voltage entering the charger module to charge the battery. The output from the battery is then insertedinto a step up step down to be regulated and the voltage is stabilized to 12 v towards the volt ampere meter input as atool to read the voltage on the battery and the current on the lamp. Based on the results of this study, it can be found thatthe blow angle of the blower against the dome 30 Â° to the dome is less effective, if the blow angle of the blower againstthe dome is 40 Â° it has good effectiveness and greatly affects the stability and speed of the dome rotation and theincrease in load applied to the dc generator results in drop voltage so it greatly affects the supply to the battery.